2005
DOI: 10.1007/s10450-005-5609-0
|View full text |Cite
|
Sign up to set email alerts
|

Bridged Polysilsesquioxane Xerogels Functionalizated by Amine- and Thiol- Groups: Synthesis, Structure, Adsorption Properties

Abstract: Bridged polysilsesquioxane xerogels containing amine ( NH 2 ; NH(CH 2 ) 2 NH 2 ; NH) and thiol ( SH) groups were synthesized by hydrolytic polycondensation of 1,2-bis(triethoxysilyl)ethane, 1,4-bis(triethoxysilyl)benzene and appropriate trifunctionalized silanes in the presence of a fluoride-ion catalyst in an ethanol solution. 29 Si CP/MAS NMR give indication of the molecular framework of these materials formed by structural T 1 , T 2 and T 3 units. 3-aminopropyl or 3-mercaptopropyl groups accessible to proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The molar ratios of TEOS/APTS and TEOS/TMPD in the reacting systems were 19:1 and 18:2. Such ratios were selected to achieve the high content of functional groups in the final materials and, in addition, to avoid fast gelation, which is often observed (even in the case of OMO samples) when the relative amount of amine-functionalized silane increases (Dąbrowski et al 2005). All synthesized samples (OMO and AFX) are non-swelling in common non-aqueous solvents.…”
Section: Synthesis Characterization and Efficiency Of Functionalizationmentioning
confidence: 99%
“…The molar ratios of TEOS/APTS and TEOS/TMPD in the reacting systems were 19:1 and 18:2. Such ratios were selected to achieve the high content of functional groups in the final materials and, in addition, to avoid fast gelation, which is often observed (even in the case of OMO samples) when the relative amount of amine-functionalized silane increases (Dąbrowski et al 2005). All synthesized samples (OMO and AFX) are non-swelling in common non-aqueous solvents.…”
Section: Synthesis Characterization and Efficiency Of Functionalizationmentioning
confidence: 99%
“…According to the literature, T units are formed by silicon atoms bonded to carbon atoms of organic groups and Q units are silicon atoms of the siloxane and silanol groups. [37][38][39] The peak assignments are presented in Table 3, and the relative abundance values of the T and Q species in the hybrid samples are presented in Table 4. It is clearly observed that the peak areas of T total species decrease from sample S50 to S75, while an increase of the peak area of Q toral species is observed.…”
mentioning
confidence: 99%
“…Cocondensation of bis(trialkoxysilane) with trifunctional alkoxysilane (in order to introduce on the surface amine-and thiol-groups) was performed successfully before and described in our previous works [21,22]. It was also determined by 13 C and 29 Si CP/MAS NMR and IR spectroscopy that xerogels contain 3-aminopropyl or 3-mercaptopropyl groups fixed to the surface by siloxane bonds.…”
Section: Resultsmentioning
confidence: 99%
“…All the synthesized xerogels were identified by IR, 13 C CP/MAS NMR and 29 Si CP/MAS NMR spectroscopy. The spectra of the samples 1, 2, 3 with detailed analysis were described by us elsewhere [22] so this would not be repeated here. Fig.…”
Section: Resultsmentioning
confidence: 99%